EMPOWERMENT OF KARANG TARUNA SARDULO SETO IN THE PRODUCTION OF ORGANIC LIQUID FERTILIZER FROM FOOD WASTE AND TOFU LIQUID WASTE AND ITS EFFECT ON THE GROWTH OF CHILI PLANTS - Fery Eko Pujiono; Tri Ana Mulyati; Deny Luvi Jayanto; Ekawati Wasis Wijayati (International Journal of Engagement and Empowerment, 2023)
Food waste and tofu liquid waste have great potential to be used as raw materials for organic liquid fertilizer. Food waste contains essential nutrients, such as nitrogen, phosphorus, and potassium, which plants need for optimal growth. Besides that, tofu liquid waste contains nutrients 1.24% N, 5.54% P2O5, 1.34% K2O, and 5.803% C-Organic which plants need so that tofu production wastewater potential to make organic fertilizer. The potential for tofu liquid waste and food waste around the Sardulo Seto youth group interested the PkM team in training on making organic liquid waste from food waste and tofu liquid waste. In this activity, several stages were carried out, namely (1) Training on Making Organic Liquid Fertilizer, (2) Assistance in the production of Liquid Organic Fertilizer, (3) Testing the Quality of Liquid Organic Fertilizer, and Testing the Growth of Chili Plants. The results show partners can improve partner understanding of utilizing waste and producing organic liquid fertilizer for food waste and tofu liquid waste very well. In addition, the results of the quality test of liquid fertilizer (PCT-14) showed pH 5, C-Organic contain 8.46%, N 4.71%, P2O5 5.78%, and K2O 2.13%. The results showed that chilies that had been treated with PCT-14 were taller than untreatted